Enhanced Lithium Storage in Reduced Graphene Oxide-supported M-phase Vanadium(IV) Dioxide Nanoparticles - Song, Hee Jo; Choi, Mingu; Kim, Jae-Chan; Park, Sangbaek; Lee, Chan Woo; Hong, Seong-Hyeon; Kim, Byung-Kook; Kim, Dong-Wan (NATURE PUBLISHING GROUP, 2016)
Vanadium(IV) dioxide (VO2) has drawn attention as one of the most attractive electrode materials for lithium-ion batteries (LIBs), hence, much research has been conducted in various sectors in this field. However, to date, most of this research has focused on the VO2(B) polymorph, whereas electrochemical information on the use of VO2(M) in LIB electrodes is insufficient. Thus, it is worthwhile to explore the possibility of using VO2(M) for LIB electrode application, and to investigate whether its electrochemical properties can be improved. In this study, VO2(M) nanoparticles, incorporated with a reduced graphene oxide composite (NP-VO2/rGO), were successfully synthesized via a sol-gel assisted hydrothermal process by the chemical reduction of V2O5 gel, using hydrazine as the reducing agent. The particle size was less than 50 nm regardless of the presence of rGO. Also, NP-VO2/rGO exhibited a specific capacity of 283 mA h g(-1) up to the 200th cycle at a current density of 60 mA g(-1), indicating its potential to be used in LIBs.
Keywords: CATHODE MATERIAL; ION BATTERIES; VO2; PERFORMANCE; COMPOSITE; NANOCOMPOSITES; NANORIBBONS; REDUCTION; GRAPHITE; CAPACITY